Topical themes and thematic progression: the “picture” of research articles - Leong, Ping Alvin (2015)
Although much has been written about the features of academic writing, there is a lack of research attention on macro issues related to the development of ideas, particularly in the writing of research articles. A concept that is useful in investigating such issues is the Hallidayan notion of theme. However, the thematic structure of research articles has received only modest attention over the years. It is also rare for thematic diagrams to be used even though they can be helpful in clarifying the thematic structure of the text. In this exploratory study, the patterning of topical themes in research articles was investigated using a diagrammatic approach. Twenty biology-related research articles were divided into t-units and analyzed for topical themes. Thematic diagrams were generated for all the articles. The diagrams revealed a progressive thematic pattern in the introduction sections of all the articles. At the whole-text level, an anchored-development pattern was observed in the majority of the articles. These findings suggest that research articles at the macro level share similarities in their thematic structure. They also shed light on how authors achieve focus in the writing through the systematic use of clause-initial elements.